CGIAR’s Expanding Role in the IPCC Seventh Assessment Report - Miranda, Daniela (2026)
Thirteen CGIAR scientists have been selected as authors for the IPCC’s Seventh Assessment Report, marking the largest CGIAR contribution to an IPCC cycle to date. This blog examines the significance of this representation and its implications for global climate policy.